Development of E-Learning-Based Blended Learning to Increase Student Learning Motivation During a Pandemic - Nugroho, Eddy Prasetyo; Hidayat, Kurniawan; Nurdin, Enjang Ali (APTISI Transactions on Management (ATM), 2023)
The impact of the Covid-19 pandemic, which began in early 2020, led to the need for online learning. This does not rule out the need for an e-learning media that requires a learning method that supports synchronous and asynchronous learning. Therefore it is necessary to develop e-learning based on blended learning that utilizes the potential of the features in the Moodle Learning Management System. The proposed development of potential features in Moodle is virtual conferences for synchronous learning and discussion forums for asynchronous learning. The use of e-learning based on blended learning aims to get good student learning motivation. To measure the impact of learning motivation, a questionnaire was administered to high school level students. The results of the questionnaire show online learning using other media such as Whatsapp groups without conducting face-to-face learning to get an average score of 1.85 which is a low criterion, while the results of the student learning motivation questionnaire after participating in e-learning based on blended learning get an average score of 3.39 which includes high criteria.